Financial sustainability and derivatives: a theoretical approach - Gabija Simaite,; Keliuotyte-Staniuleniene, Greta (Technium Social Sciences Journal, 2023)
This paper analyses the theoretical issues of financial sustainability on several levels. First of all, the variety of definitions of sustainability is discussed. After that, the concept of financial sustainability is clarified and the main elements of financial sustainability are indicated. Finally, the map of financial sustainability concepts is presented and three main approaches to financial sustainability (at international, national, and company levels) are identified. In addition, the relationship between the application of financial derivatives and a company’s financial sustainability is briefly discussed.